Growth Anthropometrics as a Metric of Malnutrition Disparities Among Young Children Affected by HIV who are Orphaned Maternally, Paternally, or Totally in Western Kenya: A Retrospective Chart Review - Shae Jansen MD; Edith Apondi MBChB, MMED; Samuel O. Ayaya MBChB, MMED; Jiae Kim PhD; Megan S. McHenry MD, MS (SAGE Publishing, 2023)
This retrospective study investigated growth outcomes of Kenyan children born to women living with HIV, comparing children who were orphaned maternally, paternally, and totally (both parents deceased) to those who were non-orphaned. We reviewed HIV clinic visits performed in Kenya from January 2011 to August 2016 in children 0 to 4 years of age. Malnutrition was assessed using stunting, underweight status, and wasting ( z -scores of ≤−2). Descriptive statistics, Chi-square, t -tests, multivariable logistic regression, and ANCOVA models were performed. Of 15 027 total children in the study population, 3.5% (n = 520) were orphaned maternally, 8.1% (n = 1222) were orphaned paternally, and 2.2% (n = 336) were orphaned totally. Children who were orphans had higher rates of malnutrition compared to non-orphans ( P  < .001). Children who were orphaned maternally and totally had lower anthropometric mean scores, presented to clinic later, and were more likely to be living with HIV. Children who are orphaned maternally or totally should be targeted in interventional strategies.